2022
DOI: 10.1093/dote/doac020
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anastomotic leak after esophagectomy: insights of an international case vignette survey and expert discussions

Abstract: Summary Anastomotic leak (AL) is a severe complication after esophagectomy. Clinical presentation of AL is diverse and there is large practice variation regarding treatment of AL. This study aimed to explore different AL treatment strategies and their underlying rationale. This mixed-methods study consisted of an international survey among upper gastro-intestinal (GI) surgeons and focus groups with expert upper GI surgeons. The survey included 10 case vignettes and data sources were integrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Our management strategies for anastomotic leak were consistent with those previously reported ( 10 , 11 ). They could be sorted into three levels: conservative management, endoscopic intervention, and reoperation, and which treatment would be performed depended on the symptoms and surgeons’ experience.…”
Section: Methodssupporting
confidence: 87%
“…Our management strategies for anastomotic leak were consistent with those previously reported ( 10 , 11 ). They could be sorted into three levels: conservative management, endoscopic intervention, and reoperation, and which treatment would be performed depended on the symptoms and surgeons’ experience.…”
Section: Methodssupporting
confidence: 87%
“…There are potential complications associated with the use of central venous catheters for thoracic drainage, including concerns that their smaller diameter may affect postoperative observations such as bleeding, anastomotic leakage, and chylothorax, potentially putting patients at risk [17][18][19] . However, recent research has shown that the modest diameter of central venous catheters generally produces little discomfort following removal, and that the lesion heals quickly.…”
Section: Complicationsmentioning
confidence: 99%
“…MIE experts, identified through a literature search in the field of MIE and previous research collaborations [ 8 , 26 28 ], were contacted to participate in this study. In total, 9 MIE experts who performed at least 120 MIEs [ 24 ] and currently perform at least 50 MIEs annually from Europe (6), the USA (2), and Asia (1) were included.…”
Section: Methodsmentioning
confidence: 99%